Reflecting on the Design Process for Virtual Reality Applications - Sutcliffe, Alistair G.; Poullis, Charalambos; Gregoriades, Andreas; Katsouri, Irene; Tzanavari, Aimilia; Herakleous, Kyriakos (My University, 2019)
A reflective analysis on the experience of virtual environment (VE) design is presented focusing on the human–computer interaction (HCI) challenges presented by virtual reality (VR). HCI design guidelines were applied to development of two VRs, one in marine archaeology and the other in situation awareness simulation experiments. The impact of methods and HCI knowledge on the VR design process is analyzed, leading to proposals for presenting HCI and cognitive knowledge in the context of design trade-offs in the choice of VR design techniques. Problems reconciling VE and standard Graphical User Interface (GUI) design components are investigated. A trade-off framework for design options set against criteria for usability, efficient operation, realism, and presence is proposed. HCI-VR design advice and proposals for further research aimed towards improving human factor-related design in VEs are discussed.
Keywords: Graphical user interfaces; Human computer interaction; Human computer interaction; Virtual reality